Psychological Stress Among Teachers and its Relation to Life Satisfaction - Qurit’e, Feras (Jordan Journal of Educational Sciences, 2017)
The purpose of this study was to identify psychological stress level among teachers, and to test mean differences in psychological stress in light of some variables, in addition to identify the relation between psychological stress among teachers and life satisfaction. The study sample consisted of (370) teachers of both genders, who were randomly selected from all schools within Directorate of Education of the North West Badia during the first semester of the academic year (2016/ 2017). Psychological stress and life satisfaction scales were employed. The findings of the study revealed that psychological stress level among teachers was medium. The study results also showed that males were more stressed than females, and short-experience teachers were more stressed than medium or long-experience teachers. Marital status was shown to have no effect on the psychological stress level. Moreover, results showed that there was significant negative relationship between psychological stress among teachers and life satisfaction